Effective photoreduction of graphene oxide for photodegradation of volatile organic compounds - Tai, Xin Hong; Chook, Soon Wei; Lai, Chin Wei; Lee, Kian Mun; Yang, Thomas Chung Kuang; Chong, Siewhui; Juan, Joon Ching (Royal Society of Chemistry, 2019)
Nowadays, humans spend most of their time indoors and are frequently exposed to volatile organic compounds (VOCs) from various sources. The photocatalytic oxidation (PCO) method is a relatively more efficient method than the adsorption method for removing VOCs from the environment. In this work, graphene oxide (GO) was partially reduced via photoreduction under ultraviolet light (UV-A) irradiation and then used as a photocatalyst to degrade VOCs. After photoreduction, the band gap of the partially reduced graphene oxide (PRGO) decreased from 3.5-4.5 eV to 3.1-4.0 eV. Methanol vapour, which acts as a model VOC, was photodegraded using the PRGO. The effectiveness of the PRGO was mainly due to the removal of oxygen functional groups and restoration of the sp2 domain. This lowered the band gap and slowed down the electron recombination rate, which resulted in a higher photocatalytic activity. The photocatalytic activity of PRGO followed pseudo-first order kinetics, with a rate constant of 0.0025 min-1, and it could be reused for five cycles without any significant loss in the photocatalytic activity. This study demonstrates the potential of PRGO as a versatile and stable metal-free photocatalyst to remove indoor pollutants. © The Royal Society of Chemistry.